Efficiency Justification for Modernizing a Grain Screw Extruder to Produce Feed Additives from Crop Residues - Doudkin, Mikhail; Kim, Alina; Vavilov, Andrey; Guryanov, Georgy; Yakovlev, Vladimir; Varavin, Yevgeniy (Engineering, Technology & Applied Science Research, 2025)
This study presents a scientific and experimental justification for improving the design of a grain screw extruder for processing crop and forestry residues. The screw assembly is the core and most sensitive part of any extruder. To transform the initial feed mixture into the finished product at the extruder output, the material passes through a series of technological processes along the screw length. The accomplishment of these processes over a shorter screw length—without compromising the product quality—reduces the processing time, construction costs, and energy consumption, while it increases productivity. This research evaluates the potential for performance improvement through modifications to the screw assembly. The justification for modernization began with theoretical investigations. Both existing and newly derived analytical equations were used to assess the screw design and its impact on the performance and efficiency when processing crop residues and ground Siberian fir needles. The study also validates the structural integrity, functionality, and technological feasibility of the modernized extruder system. The upgraded extruder was tested on a feed mixture of crushed sunflower stalks and heads, as well as fir needles, which are rich in minerals and vitamins. The tests showed that the extruder’s operation is virtually independent of the feedstock composition. The machine can be adjusted to process any type of crushed plant residue, significantly simplifying the raw material preparation for extrusion.